PHILOSOPHICAL AND SOCIOLOGICAL PERSPECTIVES OF EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
Philosophy forms the bedrock of education, which is a rapidly developing scientific discipline. Education, which has been appropriately characterised as the dynamic side of philosophy, is the primary tool of philosophy, even if the ultimate aim of philosophy is to provide explanations for the mysterious nature of the cosmos, humanity's role within it, and the myriad issues that arise from both human wisdom and foolishness. Philosophy in action is what we mean when we talk about education. The foundation of philosophy illuminates all pedagogical practices. Hence, "the art of education will never attain complete clearness without philosophy" is a highly valid observation. Both philosophy and education rely on and are affected by one another. Education follows philosophy, which lays forth the paths. Education without philosophy would be a fruitless endeavour, and philosophy without education would be severely limited. “Philosophy and education are two sides of the same coin. The former is the contemplative side while the latter is the active side,” Ross said. Philosophy is the end result of education. Philosophical questions undergird all issues in education. Simply said, educational philosophy is the study and practice of applying philosophical principles to the area of education with the goal of addressing the many challenges that arise in this domain. If you want to know why we educate (our objective), who we educate (the children), how we educate (our techniques), when we educate (our motivation), where we educate (our school), what we teach (our curriculum), and how we teach it, then you need to read educational philosophy. "An adequate philosophy of life is the foundation of a sound philosophy of education," said the author further. Education and philosophy are mutually supportive; they influence and shape one another through the ever-changing currents of ideas and deeds. Thus, "philosophy of education" refers to the process of applying overarching philosophical views to issues in the field of education.